2010
DOI: 10.1002/chem.200902371
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electronic Effect of Carbon Nanotubes in Catalysis: NH3 Synthesis with Ru Nanoparticles

Abstract: Carbon nanotubes (CNTs) have been shown to modify some properties of nanomaterials and to modify chemical reactions confined inside their channels, which are formed by curved graphene layers. Here we studied ammonia synthesis over Ru as a probe reaction to understand the effect of the electron structure of CNTs on the confined metal particles and their catalytic activity. The catalyst with Ru nanoparticles dispersed almost exclusively on the exterior nanotube surface exhibits a higher activity than the CNT-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 42 publications
7
70
0
Order By: Relevance
“…Take filling of CNTs with Ru particles as an example, a RuCl 3 /acetone solution was employed. TEM indicated that around 80% of Ru particles were distributed inside the channels following drying and reduction in H 2 , 20 which was confirmed by three-dimensional tomography. 21 The particles had a rather narrow size distribution with 90% falling in the range of 2À4 nm.…”
Section: Dispersion Of Nanoparticles Inside Cntsmentioning
confidence: 60%
See 1 more Smart Citation
“…Take filling of CNTs with Ru particles as an example, a RuCl 3 /acetone solution was employed. TEM indicated that around 80% of Ru particles were distributed inside the channels following drying and reduction in H 2 , 20 which was confirmed by three-dimensional tomography. 21 The particles had a rather narrow size distribution with 90% falling in the range of 2À4 nm.…”
Section: Dispersion Of Nanoparticles Inside Cntsmentioning
confidence: 60%
“…20 Figure 6 shows the differential electron density isosurfaces of a Ru 6 cluster inside (Ru 6 -in) and outside (Ru 6 -out) of a SWCNT (10,10). 20 Mulliken population analysis indicated that the Ru 6 -out cluster donated 1.66 electrons to the CNT convex surface whereas the inside cluster transferred 2.41 electrons to the concave surface. This is consistent with the electron structure of CNTs.…”
Section: Gas-phase Reactionsmentioning
confidence: 99%
“…Compared with the conventional synthesis methods [95][96][97], the AAO template approach shows unique advantage for hetero atom doping in CNTs [93,[98][99][100][101]. The heteroatoms can be selectively doped at the inner or outer surface of CNTs, which is very useful in many applications requiring different polar nature and chemical or physical reaction activity, such as bioseparations and catalyst supports [14,39]. This unique advantage originates from the synthesis procedure of AAO-CNTs.…”
Section: Hetero Atom Doping Of the Aao-cntsmentioning
confidence: 99%
“…Structural parameters of CNTs such as inner diameter, wall thickness, length, crystallinity, and electronic structure have a great influence on the performance of the supported particles or loaded matters [12][13][14][15]. Especially, the size of the CNT hollow core and electron density plays an important role in determining the property of the filled matters owing to the confinement effect and the difference in electron density between the exterior and interior CNT surface due to their different graphene curvature [14,16]. Some new phenomena were reported for the materials confined in CNT nanochannels, which have never been observed for their bulk counterparts [17][18][19].…”
mentioning
confidence: 99%
“…Furthermore, CNT fiber devices offer low efficiency photoelectric conversion and energy storage properties [5,13]. The deposition of a variety of metal oxides (MnO 2 [14], NiO [15], RuO 2 [16], V 2 O 5 [17], TiO 2 [3], ZnO [18]) or metal nanoparticles (Pt [19], PtRu [20], PtSn [21], Pd [22], Au [22], Ru [23], Ag [24]) onto the CNT fiber surfaces has been reported to improve the electrochemical and optical properties of CNT fibers. Metal oxides or metal nanoparticles are typically deposited randomly and inhomogeneously onto CNT fibers.…”
Section: Introductionmentioning
confidence: 99%